Dose intercomparisons between computer planning, in-vivo and phantom measurements for Iridium-192 HDR Brachytherapy - Hliziyo, Freedom (Division of Medical Physics, 2014)
During gynaecological high-dose rate (HDR) intracavitary brachytherapy (ICBT), invivo dosimetry is done to monitor the dose received by the bladder and rectum. This study was aimed at validating the need to do in-vivo dosimetry during ICBT. Thirty patients were recruited to participate in the study. Treatment setup data from the thirty patients was used to reproduce applicator and in-vivo diode treatment setups in a water phantom. Radiation doses administered to the patients were replicated in the water phantom to measure the doses at marked dose reference positions.